The Management of Acute Myocardial Infarction: Guidelines and Audit Standards: Report of a Workshop of the Joint Audit Committee of the British Cardiac Society and the Royal College of Physicians - De Bono, D P (Royal College of Physicians of London, 1994)

(untitled) (J R Coll Physicians Lond)
Successful management of acute myocardial infarction depends in the first instance on the patient recognising the symptoms and seeking help as quickly as possible. Once in hospital, fast track admission procedures and protocols for pain relief, early thrombolysis and appropriate ancillary measures (eg aspirin, IV betablockers) should be promptly instituted. Specialist advice and, if necessary, transfer to specialist units should be considered if additional complications arise. Follow-up management after discharge from hospital requires cooperation between primary and secondary care to prolong survival by reducing risk factors, using aspirin, betablockers and angiotensin converting enzyme inhibitors and instituting a suitable rehabilitation programme. Audit measures are included in the report to help general practitioners and hospital doctors review their practice and assess it against the standards set.